2002
DOI: 10.1046/j.1365-2141.2002.03507.x
|View full text |Cite
|
Sign up to set email alerts
|

DDAVP challenge tests in boys with mild/moderate haemophilia A*

Abstract: Summary. Desmopressin (DDAVP) increases plasma factor VIII coagulant activity (FVIII:C) levels in patients with mild/ moderate haemophilia A. In some subjects, FVIII can be increased to haemostatic levels, thereby avoiding use of factor VIII concentrates. We reviewed our hospital's experience with 62 boys with FVIII:C levels 0AE01-0AE3 IU/ml who had a DDAVP challenge test (i.v. 0AE3 lg/kg) following diagnosis. A therapeutic response was defined as a 1 h post-FVIII:C increase at least twofold over baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 20 publications
(24 reference statements)
4
44
3
Order By: Relevance
“…While subcutaneous injection (0.3 mg/kg) produces a similar, although slower, response to that seen with intravenous infusion, intranasal inhalation (250 mg) of DDAVP elicits a slower and less marked response, with a maximum FVIII level of *2.5-times the baseline value. Thus, the subcutaneous or intravenous routes of administration should be preferred when a maximum response is required [24,25].…”
Section: Mild Hemophilia Amentioning
confidence: 99%
“…While subcutaneous injection (0.3 mg/kg) produces a similar, although slower, response to that seen with intravenous infusion, intranasal inhalation (250 mg) of DDAVP elicits a slower and less marked response, with a maximum FVIII level of *2.5-times the baseline value. Thus, the subcutaneous or intravenous routes of administration should be preferred when a maximum response is required [24,25].…”
Section: Mild Hemophilia Amentioning
confidence: 99%
“…Young children often have markedly lower responses to desmopressin than adults, but they may become responsive at an older age. [27][28][29] The FVIII half-life, typically around 6 to 8 hours, is positively associated with basal and peak VWF antigen levels and patient age. 24 Some mutations are consistently associated with favorable responses (in particular, several of those at risk for inhibitor development; Table 1), whereas promoter, splicing, or intronic mutations respond poorly, and some missense mutations show a reduced FVIII survival 3,24-27 ( Figure 1).…”
Section: How To Reduce the Risk For Inhibitor Development In Mhamentioning
confidence: 99%
“…Although there is a certain consistency of the response within the same mutation, the response to desmopressin is somehow heterogeneous. [24][25][26][27]29 Therefore, the individual response should always be assessed by a test infusion of desmopressin with FVIII measured at least 1 and 4 hours after its administration to ascertain the pattern of response and the rate of clearance.…”
Section: How To Reduce the Risk For Inhibitor Development In Mhamentioning
confidence: 99%
“…If this had been the case, lower increases in FVIII levels after desmopressin infusion would have been seen. In a Canadian study of boys with hemophilia in whom the FVIII response initially failed after desmopressin treatment, a response was seen when they were rechallenged after a mean of 6.3 years [8]. Seary et al [9] found, in their study of 74 boys with 38 different mutations causing moderate or mild hemophilia, that age and FVIII level were strong predictors of response to desmopressin.…”
mentioning
confidence: 99%
“…While both the plasma-and platelet-derived molecules can form a functional complex, several studies demonstrate that the two cofactor pools are physically and functionally distinct [2][3][4][5][6][7]. Despite these differences, the entire platelet-derived pool of the procofactor, FV, is endocytosed from the plasma by megakaryocytes [4,8] via a two-receptor system consisting of a specific, unknown FV receptor and low density lipoprotein (LDL) receptor-related protein-1 (LRP-1) [9], an endocytic receptor belonging to a superfamily of proteins related to the LDL receptor [10]. Flow cytometric analyses and fluorescence microscopy indicate that all megakaryocytes express LRP-1 [9,11].…”
mentioning
confidence: 99%